Electrochemical Evaluation of Sustainable Corrosion Inhibitors via Dynamic Electrochemical Impedance Spectroscopy - Slepski P.; Gerengi H.; Gece, Ender Gökhan; Kaya E.; Rizvi M.; Szociński M. (American Chemical Society, 2021)
Finding suitable measurement methods for the effective management of electrochemical problems is of paramount importance, particularly for improving efficiency in corrosion protection. The need for accurate measurement techniques specific to nonstationary conditions has long been recognized, and promising approaches have emerged. This chapter introduces dynamic electrochemical impedance spectroscopy as a novel advancement in electrochemistry that can be used efficiently in galvanostatic and potentiostatic modes. The review focuses first on an explanation of the method and second on presenting a comprehensive corpus covering available studies that have applied dynamic electrochemical impedance spectroscopy for the purpose of preventing corrosion phenomena.This chapter defines the merits of this novel approach compared with the conventional electrochemical impedance spectroscopy method.